Analisis Makna Syifa’ dalam Perspektif Al-Qur’an Surah al-Isra Ayat 82 - Ahmad Syawal; Abdul Muiz Amir; Ira Trisnawati; Mansur; La Ode Man Sabdar Kanande (Gunung Djati Conference Series, 2022)
This study aims to discuss the meaning of syifa 'in Q.S al-Isra verse 82 specifically. This study uses a qualitative approach with a descriptive method of literature study. The formal object of this research is the analysis of interpretations and perspectives of the scholars, while the material object is the concept of the meaning of syifa' in Q.S al-Isra verse 82. The results of this research and discussion reveal the meaning of syifa' which is stored in the text of the verse by digging or collecting literature. interpretations put forward by the scholars. This study concludes that the Qur'an mentions itself as a healer or medicine.